2011
DOI: 10.1364/ol.36.004758
|View full text |Cite
|
Sign up to set email alerts
|

Optical-force-induced artifacts in scanning probe microscopy

Abstract: In the practice of near-field scanning probe microscopy, it is typically assumed that the distance regulation is independent of the optical signal. However, we demonstrate that these two signals are entangled due to the inherent action of optically induced force. This coupling leads to artifacts in both estimating the magnitude of optical fields and recording topographic maps.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…The final contrast of this image is a complex convolution of topography and optical properties including local and propagating plasmons of the surface. It needs to be said that several studies have shown that the interpretation of a SNOM image is indeed far from obvious and that knowledge of even hardly accessible local materials parameters is required to avoid ambiguities 31,32 . The most common artifact is induced by the strong dependence of the signal on the tip-sample distance.…”
Section: Figure 2: A) Luminescence From the Apex Of The Gold Tip B) mentioning
confidence: 99%
“…The final contrast of this image is a complex convolution of topography and optical properties including local and propagating plasmons of the surface. It needs to be said that several studies have shown that the interpretation of a SNOM image is indeed far from obvious and that knowledge of even hardly accessible local materials parameters is required to avoid ambiguities 31,32 . The most common artifact is induced by the strong dependence of the signal on the tip-sample distance.…”
Section: Figure 2: A) Luminescence From the Apex Of The Gold Tip B) mentioning
confidence: 99%
“…In addition, it is absolutely necessary to check that the detected anharmonic signal does not come from pure mechanical artifacts (tip touching the surface in tapping mode, non-harmonic tip surface interaction). 74 The second method for background suppression is based on the use of an interferometric scheme. It has been shown that in a-SNOM the final image is the result of a subtle combination of various interferometric signals.…”
Section: Fig 2 (A) (A) Uv (364 Nm) Aperture Near-field Images Of Anmentioning
confidence: 99%
“…This can, for example, be seen in Figure 5 [69]. To significantly reduce the thermal influences, this measurement was performed with an uncoated dielectric probe scanned across a structured dielectric gallium phosphide sample.…”
Section: Steady-state Oifmentioning
confidence: 99%